Penguatan Literasi Statistik Melalui Proyek Kolaborasi untuk Siswa di SMPN 2 Sunggal Deli Serdang - Mardiningsih; Sitepu, Suryati; Hasibuan, Citra Dewi; Yanti, Maulida (Jurnal Mitra Prima, 2026)
Technological advances and society's wealth of data in the information era require schools to introduce basic statistical concepts, especially statistical literacy. Statistical literacy is a person's ability to understand, interpret, and represent data in tables or graphs. Problems in SMPN 2 Sunggal include teachers experiencing difficulties in increasing student interaction in understanding statistical literacy. This activity aims to provide statistical literacy training to teachers and students through a collaborative project-based learning model. The collaborative project learning model is an innovative learning model that centers on students with varying abilities in small groups working together to improve each other's understanding. Based on the paired t-test, it was found that there was an increase in students' abilities regarding literacy statistics after learning using this method. Abstrak (Indonesia) Kemajuan teknologi dan kekayaan data masyarakat di era informasi menuntut sekolah untuk memperkenalkan konsep dasar statistika, khususnya literasi statistika. Literasi statistika adalah kemampuan seseorang dalam memahami, menginterpretasikan, dan merepresentasikan suatu data dalam bentuk tabel atau grafik. Permasalahan di SMPN 2 Sunggal diantaranya guru mengalami kesulitan dalam meningkatkan interaksi siswa/i dalam memahami literasi statistika. Kegiatan ini bertujuan untuk memberikan pelatihan literasi statistika kepada guru dan siswa/i melalui model pembelajaran proyek kolaboratif. Model pembelajaran kolaboratif merupakan model pembelajaran inovatif yang berpusat pada siswa/i dengan kemampuan bervariasi dalam kelompok kecil yang saling bekerja sama untuk meningkatkan pemahaman satu sama lain. Berdasarkan uji-t berpasangan diperoleh bahwa terjadi peningkatan kemampuan siswa/i terkait literasi statistika setelah dilakukan pembelajaran menggunakan metode ini.